Outcomes and CT Perfusion Thresholds of Mechanical Thrombectomy for Patients With Large Ischemic Core Lesions - Yang, Hongchao; Lin, Dinglai; Lin, Xiaohui; Wu, Yanmin; Yi, Tingyu; Chen, Wenhuo (Frontiers in Neurology, 2022)
Objective To explore the clinical prognosis and factors after mechanical thrombectomy(MT) in patients with large cerebral infarction assessed by computed tomographic perfusion(CTP), and the optimal threshold of cerebral blood flow(CBF) for estimating ischemic core. Methods We analyzed data from the anterior circulation database of our hospital(August 2018-June 2021). Multivariate logistic regression analyses identified the predictors of clinical outcomes for patients with large baseline infarcts(>50ml) assessed by the MIstar software. The ROC analysis was used to explore the cut-off value of factors. Results 137 patients with large baseline infarcts were included in the present study. 23(16.8%) patients achieved functionally independent outcomes, and 50(36.5%) were dead at 90 days. A total of 20(14.7%) patients had symptomatic intracranial hemorrhage (sICH). The multivariable analysis showed higher age and larger core volume were independent factors of poor outcomes. The cutoff value of core volume was 90ml, and the age was 76 years. Hypertension and rt-PA treatment were independent factors of sICH. Higher age and larger ischemic volume were independent risk factors of mortality. Conclusions MT can be applied in patients with large ischemic core volumes. Patients older than 76 years and the baseline infarcts larger than 90 ml are more likely to suffer from poor outcomes. These findings may be helpful to select patients with large baseline infarcts to be treated by MT. The threshold of CBF<30% is the independent factor, and this is worth evaluating in future studies to find the optimal threshold of CBF.